O dużych dziewczynkach i ich małych lalkach – reborn w kulturze ponowoczesnej - Zaworska-Nikoniuk, Dorota (Kultura-Społeczeństwo-Edukacja, 2012)
The article deals with the analysis of the phenomenon of simulating motherhood and fatherhood by playing reborns – realistic baby-like dolls, it describes the process of reborns creation, the intentions of artists who create them and the motives of people who use ‘artificial children’. The article gives a threefold analysis of the phenomenon: the striving for living in perfect reality that is simulated (based on the concept by J. Baudrillard), acting the play of family life in the magic world of consumption (based on the concept by G. Ritzer) and aiming at collecting experiences, impressions and emotions (based on the concept by Z. Bauman). As an educationalist I am considering the following: may using reborns have a therapeutical and educational aspect and what is their role in the postmodern world.